Study on the capture spectrum of wave energy conversion. (June 2021) - Han, Zhi; Cao, Feifei; Hann, Martyn; Gong, Haoxiang; Liu, Shangze; Li, Ming; Shi, Hongda
Highlights: A new concept, named Energy Capture Spectrum (ECS) is presented in this paper, which can evaluate the energy capture performance of any WECs in real sea state. A specific test method with no restrictions on WEC types is introduced to calculate the ECS in practical application. A physical model test based on heaving buoy was carried out to validate the correctness of ECS. The influences on the ECS by the PTO and draught of heaving buoy are studied and analyzed. Abstract: As various WECs are invented and tested, establishing wave energy farm of multiple devices is becoming a possible way to realize large-scale development of wave energy resources. Previous studies into array effects have focused on a single type of device. However, such an approach doesn't consider the potential advantages of using different device types that operate at different efficiencies for different parts of a wave spectrum within a single array to maximize the extraction of wave energy. To realize this approach, a reliable method of quantifying the energy capture performance of any WEC in real sea state is necessary. To define the energy-capture unit in an array, a new concept, named Energy Capture Spectrum (ECS) is presented. It can evaluate the energy capture performance of any WECs in real sea state by converting the power signal of the WEC into an equivalent fluctuation signal related to the incident waves at the location of the WEC and finally generates the Energy Capture Spectrum (ECS) of the WEC to compare with the incident wave spectrum. The definition of the ECS and theoretical derivation is also presented in this paper. A specific test method with no restrictions on WEC types is developed. To validate the correctness of the ECS and to study the influence on the ECS by the PTO and draught, a physical model test based on heaving buoy is introduced and analyzed. The conclusion of this paper figures out the characteristics of the ECS and optimization method of the heaving buoy device accordingly.